A modifying locus for familial adenomatous polyposis may be present on chromosome 1p35-p36. - Tomlinson, I; Neale, K; Talbot, I; Spigelman, A; Williams, C; Phillips, R; Bodmer, W (1996)
Mutations of the APC gene cause familial adenomatous polyposis (FAP) in humans and multiple intestinal neoplasia (Min) in laboratory mouse strains. A dominant modifying gene (Mom1), which partially suppresses the min phenotype, has been mapped to mouse chromosome 4. This region is syntenic with human chromosome 1p35-p36. The phospholipase A2 (Pla2s) locus is an excellent candidate for Mom1 and the equivalent human locus PLA2G2A is found on chromosome 1p35. It does not necessarily follow, however, than any modifier of mouse polyposis also influences human disease. In order to test whether a locus on 1p modifies FAP, subjects from 28 FAP families have been typed at microsatellite loci on this chromosome arm. The severity of their duodenal polyposis has also been assessed by endoscopy. Pedigree (lod score) linkage analysis found no evidence of a simple, dominant modifying gene, comparable with the action of Mom1 in inbred mouse strains. Given the more complex genetic and environmental interactions likely to exist in outbred human populations, it is probably more appropriate to use tests which do not specify a mode of inheritance. Using these methods of analysis, the data suggest that a locus on chromosome 1p35-p36 may influence the severity of duodenal FAP.